Dissecting the role of hydrogen pumping by rhenium oxide in enhancing the dehydrogenation of perhydro-dibenzyltoluene on Pt/Al2O3 - Jang, Ji Soo; Lee, Min-Woo; Lee, Seok-Ho; Jeong, Eun-Suk; Park, Tae In; Lee, Kwan-Young (Elsevier BV, 2025)
Rhenium was introduced to enhance the catalytic activity of the Pt/Al2O3 catalyst for perhydro-dibenzyltoluene dehydrogenation. The 2Pt-yRe/Al2O3 catalysts, synthesized using a sequential impregnation method, exhibited superior performance in perhydro-dibenzyltoluene dehydrogenation compared to 2Pt/Al2O3 catalysts. To elucidate the effects of rhenium oxides, various characterizations were conducted, including analyses of the structural properties of 2Pt-yRe/Al2O3 catalysts, hydrogen spillover, and electron transfer effects. Furthermore, in-situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) revealed hydrogen spillover phenomena on the catalyst surface during perhydro-dibenzyltoluene dehydrogenation. Additionally, hydrogen temperature-programmed desorption (H2-TPD) and density functional theory (DFT) calculations confirmed the spontaneous release of hydrogen on the rhenium oxide surface. These findings suggest that the addition of rhenium to the Pt/Al2O3 catalyst enhances the perhydro-dibenzyltoluene dehydrogenation activity through hydrogen spillover and pumping effects.